COVID-19;-The origin, genetics, and management of the infection of mothers and babies. Issue 1 (1st January 2020) - El-Sayyad, Hassan Ih; Abdalhafid, Yousef Ka
ABSTRACT: Coronaviruses (CoVs) are a large group of viruses infected bats and recently outbreak Wuhan, China during December 2019 and spread all over the world and infected human. It induces acute respiratory syndrome arising from the upper respiratory tract and is responsible for an elevated mortality rate in the world population. Four genetic variations are known from CoVs such as α, β, γ, and δ. SARS-CoV2 strongly related to the genomic sequences of bat and of β type. It is transmitted by droplets and contact airborne routes. The SARS-CoV-2 develops complications in pregnant women leading to cesarean delivery, but there is no recorded maternal fetal transmission of the disease. SARS-CoV-2-affected, and brain due to increase in angiotensin-converting enzyme 2 receptor on their cells. SARS-Cov-2 may appear to be a recombinant virus between the bat CoV. There are numerous drugs used for treatment of SARS-CoV-2 such as loponavir, chloroquine, , and remdesivir. Scientists encouraged for obtaining vaccine since the SARS-CoV-2 is susceptible to BCG vaccine. The vaccine development depends on the viral-coating proteins. The viral infection is highly susceptible to Lactobacilli, exosomes, and camel nanobodies. The authors recommended early investigation of pregnant women with SARS-CoV-2 and selected drugs and treatment routes to prevent complications and safeguard the unborn child during intrauterine growth.